Variability and heritability analysis in spring wheat (Triricum aestivum L .) Genotypes (Bangladesh Journal of Agricultural Research, 2015)
The experiment was carried out with 50 wheat lines to study their intergenotypic variability, heritability, GCV, PCV, genetic advance, and CV percent considering 14 morphological characters at the experimental field of Regional Wheat Research Centre RWRC), Bangladesh Agricultural Research Institute (BARI), Gazipur during November 2010 to March 2010. Significant variation was observed among the genotypes for all characters studied. High GCV and PCV values were observed for grain filling duration, grain filling rate, and seed yield. High heritability along with higher genetic advance was observed for DTH, DTA, DPM, GFD, GFR, PHT, CHLA, spikelets/spk., and yield kg/ha. The remaining traits showed lower heritability coupled with low genetic advance in percent of mean. Considering variability among the genotypes, heritability, genetic advance, percent co-efficient of variation, and field performances, the genotypes G 3, G 10, G 11, G 12, G13, G 21, G 29, G 35, G 38, G 40, G 46 and G 48 were found suitable for future breeding programme.Bangladesh J. Agril. Res. 40(3): 435-450, September 2015